Evaluation of lung ventilation distribution using electrical impedance tomography in standing sedated horses with capnoperitoneum. (July 2022) - Beazley, Shannon G.; Focken, Alex; Fernandez-Parra, Rocio; Thomas, Keri L.; Adler, Andy; Duke-Novakovski, Tanya
Abstract: Objective: To determine changes in distribution of lung ventilation with increasing intra-abdominal pressure (IAP) from carbon dioxide (CO2 ) insufflation in standing sedated horses. Study design: Prospective experimental study. Animals: A group of six healthy adult horses. Methods: Each horse was sedated with acepromazine, detomidine and butorphanol and sedation maintained with a detomidine infusion. The horse was restrained in a stocks system and a 32 electrode electrical impedance tomography (EIT) belt was wrapped around the thorax at the fifth–sixth intercostal space. EIT images and arterial blood samples for PaO2 and PaCO2, pH and lactate concentration were obtained during capnoperitoneum at 0 (baseline A), 5, 8 and 12 mmHg as IAP increased and at 8, 5, 0 (baseline B) mmHg as IAP decreased. At each IAP, after a 2 minute stabilization period, EIT images were recorded for ≥ 2 minutes to obtain five consecutive breaths. Statistical analysis was performed using anova for repeated measures with Geisser-Greenhouse correction and a Tukey's multiple comparison test for parametric data. The relationship between PaO2 and the center of ventilation in the ventral-dorsal (CoV-VD) and right-left (CoV-RL) directions or total impedance change as a surrogate for tidal volume (ΔZVT ) were tested using linear regression analysis. Significance was assumed when p ≤ 0.05. Results: There were no significant changes in CoV-VD, CoV-RL, PaO2, PaCO2, lactate concentration, pH, heart rate and respiratory rate with targeted IAP. There was a significant decrease in ΔZVT compared with baseline A at 5 mmHg IAP as IAP was increased. Conclusions and clinical relevance: Capnoperitoneum causes a significant decrease in ΔZVT in standing sedated horses with increasing IAP.